Study of termination of postprandial gastric contractions in humans, dogs and Suncus murinus: role of motilin‐ and ghrelin‐induced strong contraction. (16th September 2017) - Mikami, T.; Ito, K.; Diaz‐Tartera, H. O.; Hellström, P. M.; Mochiki, E.; Takemi, S.; Tanaka, T.; Tsuda, S.; Jogahara, T.; Sakata, I.; Sakai, T.
Abstract: Aim: Stomach contractions show two types of specific patterns in many species, that is migrating motor contraction (MMC) and postprandial contractions (PPCs), in the fasting and fed states respectively. We found gastric PPCs terminated with migrating strong contractions in humans, dogs and suncus. In this study, we reveal the detailed characteristics and physiological implications of these strong contractions of PPC. Methods: Human, suncus and canine gastric contractions were recorded with a motility‐monitoring ingestible capsule and a strain‐gauge force transducer. The response of motilin and ghrelin and its receptor antagonist on the contractions were studied by using free‐moving suncus. Results: Strong gastric contractions were observed at the end of a PPC in human, dog and suncus models, and we tentatively designated this contraction to be a postprandial giant contraction (PPGC). In the suncus, the PPGC showed the same property as those of a phase III contraction of MMC (PIII‐MMC) in the duration, motility index and response to motilin or ghrelin antagonist administration. Ghrelin antagonist administration in the latter half of the PPC (LH‐PPC) attenuated gastric contraction prolonged the duration of occurrence of PPGC, as found in PII‐MMC. Conclusion: It is thought that the first half of the PPC changed to PII‐MMC and then terminated with PIII‐MMC, suggesting that PPC consists of a digestive phase (the first half of the PPC) and a discharge phase (LH‐PPC) and that LH‐PPC is coincident with MMC. In this study, we propose a new approach for the understanding of postprandial contractions.